2011
DOI: 10.4103/0974-2077.79176
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon dioxide laser ablation followed by intralesional steroids on keloids

Abstract: Abstract:Keloid is a difficult-to-treat condition and an ideal treatment modality is not available. Carbon dioxide (CO2) laser is one of the modalities to treat keloids.Aim:To evaluate the effect of CO2 laser ablation followed by intralesional steroids on keloids.Settings and Design:This was a prospective, single-center, uncontrolled, open study.Materials and Methods:Twenty-eight patients having 35 keloids were included in the study. Keloids were ablated or excised with CO2 laser followed by intralesional ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…After thoroughly reading the full text, 56 articles that were inconsistent with the research results were excluded, and ultimately 26 articles were included. 3 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 The basic characteristics of the included studies are detailed in Table 1 . To obtain the latest pooled results, articles published since 1 January 2010 were merely included.…”
Section: Resultsmentioning
confidence: 99%
“…After thoroughly reading the full text, 56 articles that were inconsistent with the research results were excluded, and ultimately 26 articles were included. 3 , 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 The basic characteristics of the included studies are detailed in Table 1 . To obtain the latest pooled results, articles published since 1 January 2010 were merely included.…”
Section: Resultsmentioning
confidence: 99%
“…Previous surveys reported recurrence of the condition via methods like surgical excision or laser therapy . 26 Although recent studies have mentioned combination therapies for keloids like CO2 laser ablation followed by steroid injection, 27 platelet-rich plasma injection with surgical excision, 28 or plasma therapy with radiation therapy, 23 there is no consensus in this regard, and sometimes these combination therapies have led to unsuccessful outcomes or adverse effects. Choosing an effective monotherapy method can be beneficial in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Garg et al evaluated the effect of CO 2 laser ablation followed by steroid injection. 14 Their study illustrated that CO 2 laser alone was not efficient enough while adding steroid injection as adjuvant therapy could significantly reduce recurrence rate. Hersant et al reported a pilot study using platelet-rich plasma injection as adjuvant therapy to surgical excision.…”
Section: Discussionmentioning
confidence: 99%